Penilaian Kinerja dan Angka Kebutuhan Nyata Operasi dan Pemeliharaan (AKNOP) Sungai Pecangaan di Kabupaten Jepara - P.P, Pipit Skriptianata; Muhammad, Nicko Fadhil (Jurnal Talenta Sipil, 2025)
Rivers are one of the water sources that are very important for human survival. The decline in the function of river facilities and infrastructure has a significant impact on the lack of fulfillment of the need for raw water and control of the destructive power of water. Therefore, it is necessary to handle the maintenance of river facilities and infrastructure so that they can function properly, namely by conducting surveys and inventories of river facilities and infrastructure and immediately addressing the causes of the decline in the function of river facilities and infrastructure that occur. The main objective is to determine the physical condition and function of the performance assessment of river facilities and infrastructure and to obtain the ROMNF (Real Operation and Maintenance Needs Figures) needed in the OM (Operation and Maintenance) activities of a river in the future. In preparing the performance assessment and ROMNF of the river, it refers to Guidelines for Organizing Operation and Maintenance Activities for Facilities and River Maintenance, namely Circular Letter of the Director General of Water Resources No. 05/SE/D/2016. The results of the study showed that the Pecangaan River, which is 18,380 km long, has a performance assessment result of 87.97% with recommendations for preventive maintenance. Meanwhile, ROMNF 's requirement for the Pecangaan River in Jepara Regency is IDR 10,342,578,256.00.